State of power estimation of lithium-ion battery based on fractional-order equivalent circuit model. (September 2021) - Liu, Changhe; Hu, Minghui; Jin, Guoqing; Xu, Yidan; Zhai, Jun
Highlights: The fractional-order equivalent circuit model is adopted to estimate state of power (SOP). The general guidelines of the SOP constraint process under the FUDS and DST driving cycles are summarized. Novel experiments are designed to verify the SOP estimation methods. The SOP estimation based on the fractional-order equivalent circuit model provides high estimation accuracy and robustness. Abstract: State of power (SOP) is an important parameter to characterize the power performance of lithium-ion battery. Different from State of Charge (SOC), SOP estimation assumes that the battery is operated in extreme working condition, so higher accuracy and robustness are required for the battery model. In this study, the fractional-order equivalent circuit model is adopted to estimate SOP, which takes SOC, voltage, and current of the battery as constraints with the fractional-order calculus. Through the estimation results analysis under the FUDS and DST driving cycles, the general guidelines of the SOP constraint process are summarized: the discharge SOP is sequentially constrained by current, voltage, and SOC, and when the current changes frequently, the hybrid constraint is easy to be generated; the constraint process of charge SOP is opposite. Besides, novel experiments are designed separately to verify the SOP estimation results under SOC, voltage, and current constraints. The experimental results show that the maximum error of SOP estimation results is 1.34%, which proves that the SOP estimation based on the fractional-order model provides high estimation accuracy.